Bothrops jararaca venom metalloproteinases are essential for coagulopathy and increase plasma tissue factor levels during envenomation. - Karine M Yamashita; André F Alves; Katia C Barbaro; Marcelo L Santoro (Public Library of Science (PLoS), 2014)
BACKGROUND/AIMS:Bleeding tendency, coagulopathy and platelet disorders are recurrent manifestations in snakebites occurring worldwide. We reasoned that by damaging tissues and/or activating cells at the site of the bite and systemically, snake venom toxins might release or decrypt tissue factor (TF), resulting in activation of blood coagulation and aggravation of the bleeding tendency. Thus, we addressed (a) whether TF and protein disulfide isomerase (PDI), an oxireductase involved in TF encryption/decryption, were altered in experimental snake envenomation; (b) the involvement and significance of snake venom metalloproteinases (SVMP) and serine proteinases (SVSP) to hemostatic disturbances. METHODS/PRINCIPAL FINDINGS:Crude Bothrops jararaca venom (BjV) was preincubated with Na2-EDTA or AEBSF, which are inhibitors of SVMP and SVSP, respectively, and injected subcutaneously or intravenously into rats to analyze the contribution of local lesion to the development of hemostatic disturbances. Samples of blood, lung and skin were collected and analyzed at 3 and 6 h. Platelet counts were markedly diminished in rats, and neither Na2-EDTA nor AEBSF could effectively abrogate this fall. However, Na2-EDTA markedly reduced plasma fibrinogen consumption and hemorrhage at the site of BjV inoculation. Na2-EDTA also abolished the marked elevation in TF levels in plasma at 3 and 6 h, by both administration routes. Moreover, increased TF activity was also noticed in lung and skin tissue samples at 6 h. However, factor VII levels did not decrease over time. PDI expression in skin was normal at 3 h, and downregulated at 6 h in all groups treated with BjV. CONCLUSIONS:SVMP induce coagulopathy, hemorrhage and increased TF levels in plasma, but neither SVMP nor SVSP are directly involved in thrombocytopenia. High levels of TF in plasma and TF decryption occur during snake envenomation, like true disseminated intravascular coagulation syndrome, and might be implicated in engendering bleeding manifestations in severely-envenomed patients.